2001
DOI: 10.1097/00004836-200109000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Endoscopic Features of Adult T-cell Leukemia/Lymphoma With Duodenal Involvement

Abstract: We describe three cases of adult T-cell leukemia/lymphoma (ATLL) with duodenal involvement and provide a review of the literature. The first case, a 74-year-old woman with acute subtype of ATLL, had multiple polypoid lesions from the bulbus extending into the descending portion of the duodenum. The second case, a 70-year-old man with lymphoma subtype of ATLL, had a polypoid tumor in the descending portion of the duodenum and multiple protruded lesions in the small and large intestines. The third case, a 67-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In addition to the prior categories, tumor type [8,15] and colitis type [12] have been reported. A search of the MEDLINE database retrieved only 5 reported cases of ATLL with MLP [5,[9][10][11]13] . Although the molecular mechanisms which may influence phenotypes [8] 60/M ND Ulcerated tumor ND 15 mo, died Itsuno [9] 43/M Gastric ulcerated tumors MLP CPA, DXR, VCR 8 mo, died Gakiya [10] 62/M Duodenal MLP MLP CPA, PSL 1 mo, alive Isomoto [11] 70/M Duodenal polypoid tumor MLP CPA, DXR, VDS, VP-16 4 mo, alive Isomoto [12] 47/M Gastric protruding masses Granular, friable, and hyperemic mucosa CPA, DXR, VCR, PSL 12 mo, died Isomoto [13] 58/F Normal MLP CPA, DXR, VDS 7 mo, died Asada [14] 78/F ND Reddish, flat or slightly elevated lesion CPA, THP, VCR, VP-16 died Hidaka [15] 68/M ND Ulcerated tumor surgery, CPA, DXR, VDS, PSL 10 mo, alive Onishi [16] of colonic lesions have not been clarified, colonic MLP may be correlated with coexistence of upper gastrointestinal MLP or polypoid lesions (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the prior categories, tumor type [8,15] and colitis type [12] have been reported. A search of the MEDLINE database retrieved only 5 reported cases of ATLL with MLP [5,[9][10][11]13] . Although the molecular mechanisms which may influence phenotypes [8] 60/M ND Ulcerated tumor ND 15 mo, died Itsuno [9] 43/M Gastric ulcerated tumors MLP CPA, DXR, VCR 8 mo, died Gakiya [10] 62/M Duodenal MLP MLP CPA, PSL 1 mo, alive Isomoto [11] 70/M Duodenal polypoid tumor MLP CPA, DXR, VDS, VP-16 4 mo, alive Isomoto [12] 47/M Gastric protruding masses Granular, friable, and hyperemic mucosa CPA, DXR, VCR, PSL 12 mo, died Isomoto [13] 58/F Normal MLP CPA, DXR, VDS 7 mo, died Asada [14] 78/F ND Reddish, flat or slightly elevated lesion CPA, THP, VCR, VP-16 died Hidaka [15] 68/M ND Ulcerated tumor surgery, CPA, DXR, VDS, PSL 10 mo, alive Onishi [16] of colonic lesions have not been clarified, colonic MLP may be correlated with coexistence of upper gastrointestinal MLP or polypoid lesions (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, gastrointestinal involvement of ATLL was reported to be one of the poor prognostic factors in acute type ATLL [11,24] . Therefore, endoscopic evaluation may be important for estimating prognosis of ATLL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Itsuno et al [7] reported a case of ATLL accompanied by several ulcerative tumorous lesions in the terminal ileum. More recently, we have reviewed the endoscopic findings of duodenal involvement by ATLL and documented that 92% (12 of 13) of the ATLL cases involving the duodenum had protruded (mostly polypoid) lesions [11]. These were often multifocal, typically manifesting as multiple lymphomatous polyposis [11].…”
Section: Discussionmentioning
confidence: 99%
“…5). Pulmonary, CNS, and intestinal involvement are variably reported (Isomoto et al, 2001), as well as more unusual extranodal sites (Shimamoto and Yamaguchi, 1992).…”
Section: Adult T-cell Leukemia/lymphomamentioning
confidence: 99%
“…Hypercalcemia is described in $30-60% of patients with ATLL, and is frequently associated with lytic bone lesions (Isomoto et al, 2001;Yamaguchi et al, 1990).…”
Section: Adult T-cell Leukemia/lymphomamentioning
confidence: 99%